Creature of Flame Retardant Textile Materials Based on the Grafted Copolymers - Karina, Shadiyeva; Sadiqov, А. I.; Ozodakhon, Yuldosheva (European Journal of Life Safety and Stability (2660-9630), 2021)
The creation of fire-resistant textile materials obtained on the basis of grafted copolymers, the improvement of physic-chemical and fire-technical properties.